2014
DOI: 10.1016/j.bbamcr.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Activation of inflammasomes in podocyte injury of mice on the high fat diet: Effects of ASC gene deletion and silencing

Abstract: Inflammasome, an intracellular inflammatory machinery, has been reported to be involved in a variety of chronic degenerative diseases such as atherosclerosis, autoinflammatory diseases and Alzheimer’s disease. The present study hypothesized that the formation and activation of inflammasomes associated with apoptosis associated speck-like protein (ASC) are an important initiating mechanism resulting in obesity-associated podocyte injury and consequent glomerular sclerosis. To test this hypothesis, Asc gene knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 59 publications
(79 reference statements)
5
75
0
Order By: Relevance
“…However, we speculate that the diet-induced increased production of inflammatory cytokines, such as IL-1β and IL-18, resulting from activation of NALP3 inflammasomes, the mouse kidney attenuated both renal injury (histology) and dysfunction (albuminuria) caused by HD. Consistent with our results, a recent study showed that a high-fat diet increases NLRP3 inflammasome activity in glomeruli, resulting in glomerular inflammation and consequent glomerular injury (30). Moreover, we previously observed a and hepatic steatosis was associated with local activation of NLRP3 inflammasome.…”
Section: Discussionsupporting
confidence: 80%
“…However, we speculate that the diet-induced increased production of inflammatory cytokines, such as IL-1β and IL-18, resulting from activation of NALP3 inflammasomes, the mouse kidney attenuated both renal injury (histology) and dysfunction (albuminuria) caused by HD. Consistent with our results, a recent study showed that a high-fat diet increases NLRP3 inflammasome activity in glomeruli, resulting in glomerular inflammation and consequent glomerular injury (30). Moreover, we previously observed a and hepatic steatosis was associated with local activation of NLRP3 inflammasome.…”
Section: Discussionsupporting
confidence: 80%
“…Caspase-1 was also demonstrated to promotes atherosclerosis in apolipoprotein E-null [Apoe( -/ -)] mice by enhancing the inflammatory status of the lesion through a mechanism likely involving activation of lesion-associated immune cells and expression of cytokines, including interferon-c and IL-1b (4,44). In addition to Nlrp3, Nlrp1 has also been implicated in the regulation of immune-inflammatory processes in arterial ECs, contributing to endothelial activation and vessel remodeling (3).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that Nlrp3 inflammasome activation is critical for the development of atherosclerosis on endogenous danger factors such as cholesterol crystals (10,29). Cholesterol crystals can be found in all stages of atherogenesis and is present in early atherosclerotic lesions (10,36) and in obese mice (4). Engulfment of cholesterol crystals by macrophage leads to lysosomal destablization and cathepsin B release (10), which results in Nlrp3 inflammasome activation and canonical inflammatory effects, including recruitment and infiltration of inflammatory cells into vasculature and subsequent vascular inflammation and injury (10).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial reactive oxygen species (ROS) activate NLRP3 inflammasomes under conditions of high glucose or advanced glycation end-product stressed podocytes 158 . ASC is a component of NLRP3 inflammasome and shRNA-transfection of Asc in mice on a high fat diet attenuates proteinuria, albuminuria, foot process effacement of podocytes and loss of podocyte slit diaphragm molecules 175 . Human podocytes cultured with sera from normoalbuminuric patients with T1DM and high LPS activity show downregulation of 3-phosphoinositide-dependent kinase-1 (PDK1), an activator of the Akt cell survival pathway, and induction of apoptosis 148 .…”
Section: Review Criteriamentioning
confidence: 99%